Finite deformations govern the anisotropic shear-induced area reduction of soft elastic contacts. (October 2020) - Lengiewicz, J.; de Souza, M.; Lahmar, M.A.; Courbon, C.; Dalmas, D.; Stupkiewicz, S.; Scheibert, J.
Highlights: Modelling of and experiment on the evolution of contact area between soft solids under shear. Computational finite-deformation model combining non-adhesive contact and non-linear elasticity. Anisotropic area reduction quantitatively reproduced by the model with no adjustable parameter. Three elementary mechanisms revealed: local contact lifting (main contributor), contact laying and in-plane deformation. The findings are supported by an original experiment employing particle-tracking analysis. Graphical abstract: Abstract: Solid contacts involving soft materials are important in mechanical engineering or biomechanics. Experimentally, such contacts have been shown to shrink significantly under shear, an effect which is usually explained using adhesion models. Here we show that quantitative agreement with recent high-load experiments can be obtained, with no adjustable parameter, using a non-adhesive model, provided that finite deformations are taken into account. Analysis of the model uncovers the basic mechanisms underlying anisotropic shear-induced area reduction, local contact lifting being the dominant one. We confirm experimentally the relevance of all those mechanisms, by tracking the shear-induced evolution of tracers inserted close to the surface of a smooth elastomer sphere in contact with a smooth glass plate. Our results suggest that finite deformations are an alternative to adhesion, when interpreting a variety of sheared contact experiments involving soft materials.